Analisis Implementasi pasal 35 Ayat (1) UU Ketenagakerjaan Tahun 2003 dalam Merekrut Tenaga Kerja yang Sesuai dengan Kebutuhan Perusahaan - Suhartini Suhartini; Andriani Andriani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the implementation of Article 35 Paragraph 1 of the Employment Law No. 13 of 2003 in the workforce recruitment process at PT. Fatikha Jagat of Fortune. By using case study methods and a qualitative approach, this research understands how companies apply these legal provisions in recruitment and selection practices. The research results show that PT. Fatikha Jagat Rezeki has taken strategic steps in recruiting workers who suit the company's needs, while maintaining workers' rights during the recruitment process. However, research also identifies several challenges in implementing these legal provisions, such as varying understanding among management and employees regarding labor regulations. Therefore, this research recommends additional training for HR and management teams regarding labor regulations and the importance of protecting workers' rights. The results of this research can provide valuable insights for other companies in creating better and more sustainable recruitment practices.